Answer:
-122
Step-by-step explanation:
The common difference is
-5-(-2)
-3
So
a+(n-1)d
-2+(41-1)-3
-2+(-120)
-122
Quadratic formula = (-b +- sqrt(b^2 - (4ac))) / 2a
![\frac{ -12 + \sqrt{(12)^2 -((4)(9)(-24))}}{2(9)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20-12%20%2B%20%20%5Csqrt%7B%2812%29%5E2%20-%28%284%29%289%29%28-24%29%29%7D%7D%7B2%289%29%7D%20)
and
![\frac{ -12 - \sqrt{(12)^2 -((4)(9)(-24))}}{2(9)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20-12%20-%20%5Csqrt%7B%2812%29%5E2%20-%28%284%29%289%29%28-24%29%29%7D%7D%7B2%289%29%7D%20)
then simplify and solve
Use the FOIL method: First, Outside, Inside, Last
3x(2x) = 6x²
3x(-4) = -12x
3(2x) = 6x
3(-4) = -12
6x² -12x + 6x-12
Combine like terms
-12x + 6x = -6x
6x² - 6x - 12 is your answer
hope this helps